ANALISIS HUBUNGAN PROFITABILITAS DAN HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2016 - Ivana Nina Esterlin Barus, Gusniyanti, Mardiana, (EKONOMIA, 2020)
A company in conducting stock valuation analysis, there are two approaches used namely fundamental analysis and technical analysis.This study aims to determine the relationship of profitability as measured by return on assets (ROA) and the share price of a Banking Company listed on the Indonesia Stock Exchange (BEI) for the period 2012-2016.The analytical tool used in this study is the analysis of correlation coefficients.The results of this study indicate that from the results of the correlation coefficient analysis return on assets (ROA) and stock prices, the probability number is 0.000, Pearson correlation (r) 0.467, R Square (r2) 0.218089, and tcountÂ  5.857, ttable totaling 1,979 shows that there is a correlation between return on assets (ROA) and stock prices. Furthermore, the positive correlation of 0.467 indicates that return on assets (ROA) has a positive correlation to stock prices, so the greater the return on assets (ROA) generated, the greater the stock price, because the correlation value is below the 0.5 then the correlation between these two variables is considered moderate. The conclusion of this study is the hypothesis accepted.